Recaudación tributaria y su relación con la ejecución del gasto público en la Municipalidad Distrital de San Juan Bautista, periodo 2019 – 2022 - Chota Angulo, Talhia Estefani (2024)
The collection of municipal taxes is a very important tool within the management of any municipality, as it allows it to capture the financial resources necessary to finance the public expenditure of all the activities that will be carried out over a period of time. and in this way, the objectives and goals established by senior management are met. The study includes the development of a research titled "Tax collection and its relationship with the execution of public spending in the District Municipality of San Juan Bautista, period 2019 - 2022", its attention is focused mainly on being able to determine the relationship between the collection of municipal taxes with the public expenditure executed. A quantitative methodology was used under the approach of a descriptive correlational design, in this case the registration form was the instrument used which allowed the data to be collected for corresponding analysis based on a period of four years (2019 2022). From the analysis carried out, the research reveals an intense negative relationship between the study variables, according to the Spearman's Rho correlation coefficient, which was calculated at -0.776.